Global Trends and Evolution of Non-Formal Education Research (1977–2025): A Bibliometric Analysis - Yasinta Luthfianti; Anan Sutisna; Awaluddin Tjalla; Riyan Arthur; Irwanto (Indonesian Journal of Instruction, 2026)
The rapid expansion of Non-Formal Education (NFE) research has not been accompanied by a comprehensive understanding of its intellectual structure, thematic evolution, and collaboration patterns over time. This gap limits the ability to position NFE as a strategic field in addressing complex global challenges. This study aims to analyze, map, and evaluate the intellectual structure, thematic evolution, and social network patterns of global NFE research from 1977 to 2025. This study employed a bibliometric research design using the PRISMA protocol to systematically select 410 Open Access articles indexed in Scopus. Data were collected through database extraction and analyzed using bibliometric coupling and co-word analysis supported by Bibliometrix and VOSviewer. The findings reveal an accelerating growth of publications (7.93% annually), driven by global agendas such as the SDGs and the COVID-19 pandemic. Thematically, NFE has evolved from a predominantly pedagogical domain into an interdisciplinary field intersecting with public health, environmental sustainability, and gender empowerment. Knowledge structures are increasingly shaped by media literacy and inclusion, while conflict resolution and diversity management emerge as growing themes. However, collaboration networks remain fragmented, forming academic silos dominated by specific regional clusters. This study concludes that strengthening cross-regional collaboration, particularly through South–South partnerships, is essential to enhance knowledge integration and reposition NFE as a key instrument for social cohesion beyond its traditional technical role.